Selection of novel peptides homing alternative targets in triple negative breast cancer - Ferreira, Débora (2017)
[Excerpt] Breast cancer is the most frequent cancer amongst women, representing 25% of all cancer cases, with an estimated 1.67 million new cases in 2012 1. Phenotypically characterized by the lack of known receptors, the triple negative breast cancer (TNBC) subtype is responsible for 10 to 20% of all diagnosed breast cancers 2. Due to its unique profile, aggressive behavior and different patterns of metastasis, the search for effective diagnosis and treatment tools has intensified 3. However, the lack of specific cell targeting remains the main barrier for sensitive diagnostic tools. [...]